Diagnostic Value of Serum d-Dimer Level for Tubo-Ovarian Abscess: A Cross-Sectional Pilot Study. (August 2015) - Yilmaz, Bulent; Kasap, Burcu; Demir, Mustafa; Gungorduk, Kemal; Kelekci, Sefa; Sutcu, Recep
Aim of this study is to investigate the diagnostic role of serumd -dimer levels for tubo-ovarian abscess (TOA). Patients diagnosed with TOA (n = 36) and matched controls with ovarian cysts (n = 39) were collected prospectively. Patients in the 2 groups were compared on the basis of size of TOA or cyst, demographic characteristics, and serumd -dimer levels. Baseline characteristics of both groups were comparable. Meand -dimer levels were significantly higher ( P < .0001) in patients with TOA (1870.6 ± 2401.7 ng/mL) when compared to adnexal cyst group (164.4 ± 81.1 ng/mL).d -Dimer had a diagnostic value of 99.9%, specificity of 100.0%, and sensitivity of 97.4% based on a cutoff value 314 ng/mL for predicting TOA. In conclusion, serumd -dimer level was significantly elevated in women with TOA compared with benign adnexal cysts. Thus, this inexpensive, feasible, and reproducible marker can be used for differential diagnosis of TOA.